Eksplorasi dan Potensi Jamur Pelarut Fosfat pada Andisol Terkena Dampak Erupsi Gunung Sinabung dengan Beberapa Ketebalan Abu di Kecamatan Naman Teran Kabupaten Karo - Viky Fatmala; Mariani Sembiring; Jamilah Jamilah (Universitas Sumatera Utara, 2015)
This research was conducted to determine the type of Phosphate Solubilizing Fungi (PSF) as a result from isolated Andisol in Naman Teran district Karo sub district that affected by the eruption of mount Sinabung with some ash thickness around 0 cm (not affected), >0 cm - <2 cm (thin), >2 cm - 8 cm (moderate) and >8 cm (thick), and to determine its ability to dissolve phosphate on solid media. Isolation and potential test on solid media using media Pikovskaya with phosphate source Ca3(PO4)2. Evaluates JPF potential qualitatively by measuring the holozone diameter using index values dissolution. The results were obtained 4 PSF genus found in Andisol’s soil affected by the eruption of mount Sinabung: Aspergillus sp., Trichoderma sp., Penicillium sp.1 and Penicillium sp. 2. PSF were able to survive up to a thickness of Asharound >8cm is Aspergillus sp. Based on the test results the potential of solid media Penicillium sp.2 has the best ability to dissolve phosphate.Keyword: phosphate, volcanic ash, phospate solubilizing fungi